2022
DOI: 10.1186/s12905-022-01615-2
|View full text |Cite
|
Sign up to set email alerts
|

Women's interdependence after hysterectomy: a qualitative study based on Roy adaptation model

Abstract: Background Hysterectomy is a difficult process that some women encounter that can affect their interdependence, but its impact on women’s Interdependence has received less attention. Therefore, this study aimed to explain women’s Interdependence after hysterectomy. Methods This qualitative study was performed using a directed content analysis approach in Mashhad (Iran). Thirty women with a history of hysterectomy were included in the study by purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…The time coming up to surgery was a time of thinking about who they were going to be following the procedure, which added additional stress for the participants for whom the uterus was viewed as essential to being a full woman. On the other hand the current study are inconsistent with (Goudarzi et al, 2022), who applied their study on Iranian women's selfconcept after hysterectomy who reported that, In how Iranian women were viewed, the uterus was significant. The hysterectomy affected the body.…”
Section: Discussioncontrasting
confidence: 96%
“…The time coming up to surgery was a time of thinking about who they were going to be following the procedure, which added additional stress for the participants for whom the uterus was viewed as essential to being a full woman. On the other hand the current study are inconsistent with (Goudarzi et al, 2022), who applied their study on Iranian women's selfconcept after hysterectomy who reported that, In how Iranian women were viewed, the uterus was significant. The hysterectomy affected the body.…”
Section: Discussioncontrasting
confidence: 96%
“…Support in the form of motivation and enthusiasm also increase self-confidence. In line with this theme, Goudarzi et al (2022) showed that most posthysterectomy women experience fear and helplessness, prompting them to find strength and protection. Support and assistance from a partner increases the emotional direction for better ambitions, augment coition relationship, and reduce psychological problems (Askew & Zam, 2013).…”
Section: Resultsmentioning
confidence: 78%
“…Self-criticism can help people learn from mistakes and overcome flaws or undesirable behaviors (Joeng and Turner, 2015). Goudarzi et al (2022) found women believe that the loss of the uterus will make them feel deprived, causing them to be concerned about their marital connection. The partner's reaction to their illness is the source of concern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the hysterectomy, it is recommended that family members be consulted to ensure the emotional support and care of women after the hysterectomy. It can help the adaptation to hysterectomy (22). Real experience of women after hysterectomy is related on comprehensive consideration before hysterectomy (a. disease factors; b. fertility factors; c. opinions of others); emotions and experience after hysterectomy (a.…”
Section: Discussionmentioning
confidence: 99%